On the Uses of Authenticity - Mak, Bonnie (Archivaria, 2012)
Scholars and professionals across the disciplines have adopted the concept of authenticity to help focus growing concerns about the digital preservation of archival materials, but authenticity itself remains a major point of controversy in these debates. The present article offers an alternative view of the impasse by investigating a similar moment of disquiet in the early modern period. In these prior contests, disagreements about authenticity emerged as an effective way to renegotiate the social order. Scholars proposed and tested different senses of authenticity, vowing temporary allegiance to the one that suited their particular case. By examining some of these feuds, this article demonstrates that arguments about authenticity can function as a means of instigating social change, and suggests that this understanding of authenticity may productively be brought to bear on contemporary discussions about the curation and use of digitally encoded materials. RÉSUMÉ  Les spécialistes et les professionnels de plusieurs disciplines ont adopté le concept d’authenticité afin de mieux cerner les préoccupations émergentes au sujet de la préservation numérique des documents d’archives, mais l’authenticité elle-même demeure un point de controverse dans ces débats. Cet article présente un autre point de vue de l’impasse en examinant un moment similaire au début des temps modernes. Dans ces débats précédents, les différences d’opinion au sujet de l’authenticité sont devenues une façon efficace de renégocier l’ordre social. Des spécialistes ont proposé et évalué différentes notions de l’authenticité, adoptant de façon temporaire celle qui convenait le mieux à leurs besoins particuliers. En examinant ces conflits, l’article montre que les débats au sujet de l’authenticité peuvent servir de moyen pour inciter un changement social et il suggère qu’on peut se servir de cette connaissance de l’authenticité dans les discussions contemporaines au sujet de la conservation et de l’utilisation de données à codage numérique.